2013
DOI: 10.1172/jci71165
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the TRPC5 ion channel protects the kidney filter

Abstract: An intact kidney filter is vital to retention of essential proteins in the blood and removal of waste from the body. Damage to the filtration barrier results in albumin loss in the urine, a hallmark of cardiovascular disease and kidney failure. Here we found that the ion channel TRPC5 mediates filtration barrier injury. Using Trpc5-KO mice, a small-molecule inhibitor of TRPC5, Ca 2+ imaging in isolated kidney glomeruli, and live imagining of podocyte actin dynamics, we determined that loss of TRPC5 or its inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
184
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(188 citation statements)
references
References 58 publications
(94 reference statements)
4
184
0
Order By: Relevance
“…53 In concordance with our findings, a number of recent works has established a nephrinindependent pathway resulting in Rac activation as an important pathomechanism to drive effacement. 13,54,55 Instead, we find that foot process recovery is impaired in nephrin Y3F/Y3F animals in both injury models, similar to that observed in mice lacking the actin regulators synaptopodin and cofilin. 56,57 Taken together, our data support a model wherein nephrin tyrosine phosphorylation is required to counteract normal podocyte stress and loss of this phosphorylation, as seen in nephrin Y3F/Y3F mice and some human diseases, leads to irreversible injury and chronic disease.…”
Section: Discussionsupporting
confidence: 78%
“…53 In concordance with our findings, a number of recent works has established a nephrinindependent pathway resulting in Rac activation as an important pathomechanism to drive effacement. 13,54,55 Instead, we find that foot process recovery is impaired in nephrin Y3F/Y3F animals in both injury models, similar to that observed in mice lacking the actin regulators synaptopodin and cofilin. 56,57 Taken together, our data support a model wherein nephrin tyrosine phosphorylation is required to counteract normal podocyte stress and loss of this phosphorylation, as seen in nephrin Y3F/Y3F mice and some human diseases, leads to irreversible injury and chronic disease.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, Gq-coupled signaling cascades activate other TRPC family members including TRPC5 (54), which further enhances intracellular calcium levels and promotes RAC1 activation (3,4). Both Rho A and RAC1 modulate cytoskeletal dynamics and play critical roles in regulating glomerular filtration barrier integrity (3,(55)(56)(57)(58)(59). Gq signaling also stimulates CN (26,60) and causes a decrease in glomerular podocytes by mechanisms that are dependent on gene transcription (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Greka et al have shown that TRPC5-mediated calcium influx is required for RAC1 activation in response to angiotensin II in podocytes (75) and that RAC1 increases trafficking of TRPC5 to the plasma membrane (40). Moreover, just as inhibition of TRPM2 reduces kidney injury in response to ischemia, inhibition of TRPC5 reduces proteinuria in response to protamine sulfate or LPS (76).…”
Section: Discussionmentioning
confidence: 99%